A novel donor–acceptor structured diketopyrrolopyrrole-based conjugated polymer synthesized by direct arylation polycondensation (DArP) for highly efficient antimicrobial photothermal therapy. (2nd February 2023) - Wu, Zhihui; Wang, Jing; Zhao, Linlin; Li, Chenxi; Lu, Yan
Abstract : Novel photothermal conjugated polymers with unique two alternating D–A pairs along backbone was synthesized by direct arylation polycondensation (DArP), achieving highly efficient sterilization. Abstract : A novel donor (D)–acceptor (A) structured conjugated polymer (PDPP-TP), which contains two alternating D–A pairs, namely thiophene (T)-diketopyrrolopyrrole (DPP) and thiophenen (T)-thieno[3, 4- b ]pyrazine (TP) along the main chain of the polymer, was synthesized by direct arylation polycondensation (DArP) for a highly efficient photothermal antibacterial treatment. The hydrophilic PDPP-TP-based nanoparticles (PTNPs) with a hydration diameter of about 120 nm were obtained by self-assembly using DSPE-mPEG2000 as the polymer matrix. PTNPs show strong near-infrared (NIR) absorbance with a λ max at 910 nm ( ε = 2.25 × 10 4 L mol −1 cm −1 ) and NIR light-triggered photoactivity with a high photothermal conversion efficiency (PTCE) of 52.8% under 880 nm laser irradiation. Keeping the merits of excellent biocompatibility and photostability, PTNPs exhibited remarkable bacterial inhibition efficiency of almost 100% against Gram-negative E. coli and Gram-positive S. aureus with the help of an 880 nm laser (0.7 W cm −2, 6 min), demonstrating its great potential as photothermal materials with a broad spectrum of activity for the effective treatment of microbial infections.